2011
DOI: 10.1016/j.pneurobio.2011.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Activity-regulated genes as mediators of neural circuit plasticity

Abstract: Modifications of neuronal circuits allow the brain to adapt and change with experience. This plasticity manifests during development and throughout life, and can be remarkably long lasting. Many electrophysiological and molecular mechanisms are common to the seemingly diverse types of activity-dependent functional adaptation that take place during developmental critical periods, learning and memory, and alterations to sensory map representations in the adult. Experience-dependent plasticity is triggered when n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
87
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(93 citation statements)
references
References 262 publications
(387 reference statements)
4
87
1
1
Order By: Relevance
“…18,19 Psychostimulant-regulated immediate-early genes (IEGs) include both transcription factors of the Fos/Jun/Egr families as well neuronally-enriched genes such as Arc, Bdnf and Cdk5 that play direct roles in the plasticity of synaptic strength and structure. [19][20][21][22] We have shown that amphetamine increases expression of Fos/ Jun family transcription factors in the striatum of both WT and MUT mice of the Mecp2 308 strain, demonstrating that expression of wild-type MeCP2 is not required for the IEG response. 7 However, both the magnitude of FosB and JunB induction following a single dose of amphetamine and the plasticity of Fos, FosB and JunB inducibility following repeated amphetamine is significantly altered in Mecp2 MUT mice.…”
Section: Mutation Of Mecp2 Alters Transcriptional Regulation Of Selecmentioning
confidence: 91%
“…18,19 Psychostimulant-regulated immediate-early genes (IEGs) include both transcription factors of the Fos/Jun/Egr families as well neuronally-enriched genes such as Arc, Bdnf and Cdk5 that play direct roles in the plasticity of synaptic strength and structure. [19][20][21][22] We have shown that amphetamine increases expression of Fos/ Jun family transcription factors in the striatum of both WT and MUT mice of the Mecp2 308 strain, demonstrating that expression of wild-type MeCP2 is not required for the IEG response. 7 However, both the magnitude of FosB and JunB induction following a single dose of amphetamine and the plasticity of Fos, FosB and JunB inducibility following repeated amphetamine is significantly altered in Mecp2 MUT mice.…”
Section: Mutation Of Mecp2 Alters Transcriptional Regulation Of Selecmentioning
confidence: 91%
“…4. In most cases, plasticity regulation involves signalling pathways relating neuronal activity to the expression of key activity-regulated genes [71][72][73] . Consistent with its central roles in mediating signalling downstream of synaptic activity, calcium has prominent roles in activity-regulated gene expression.…”
Section: Plasticity Regulationmentioning
confidence: 99%
“…This heterogeneity poses major challenges to the study of neural coding in general and neural plasticity in particular. In the context of plasticity, one way to deal with such heterogeneity is to study the same neurons repeatedly, an approach that has proven highly useful in anatomical studies (8,10,(25)(26)(27)(28)(29)(30)(31). Thus, we devised a way to study the physiology of single cells over long time scales.…”
Section: Resultsmentioning
confidence: 99%